ANÁLISE DO ÍNDICE DE SATISFAÇÃO DOS EXPOSITORES E VISITANTES NA 18ª FENASOJA - Büttenbender, Bruno; Zamberlan, Luciano; Endler, Amanda C.; Riedner, Karin; Schonhart, Anelize; Graef, Cleber E. (Salão do Conhecimento, 2013)
Resumo